Gender sensitive teaching among selected junior high school teachers in Iloilo City - Gaitan, Obed Joy Benignos (University of the Philippines Visayas, 2018)
Gender equality is a human right and women should be treated as partners of men in nation-building as stated in the Philippines' Republic Act of 7192 and aims to promote gender equality and empower women and girls which is the fifth among the 17 Sustainable Development goals set by UN. On this premise, this study explored how the selected Junior High School teachers in Iloilo City demonstrated gender sensitive classroom practices that promote gender sensitive learning specifically, if they are (a) aware of gender concepts, if their (b) instructional behaviors are from a gender-sensitive perspective, and if they (c) employ teaching strategies that promote gender-perspective interaction. Data were gathered using self-assessment questionnaire, classroom observation and themes that were taken from the focus group discussion to project the existence of the said environment. Ten junior high school teachers were chosen to be part of the study who taught the subject in their field for two years or more. Results revealed that teachers are aware of gender concepts, their instructional behaviors showed gender sensitive perspective and finally, they employ strategies for teaching their lessons. However, there is lack of specific strategies to teach gender concepts and teaching these concepts is not yet mainstreamed in the curriculum and not explicitly included in the learning outcomes. Seminars and trainings about gender sensitivity are powerful avenues for teachers to be equipped to bridge the gap between cognitive knowledge and creating a gender sensitive learning environment.